2021
DOI: 10.3390/rs13193804
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Inland Water Bodies along Altimetry Tracks for Estimating Surface Water Storage Variations in the Congo Basin

Abstract: Surface water storage in floodplains and wetlands is poorly known from regional to global scales, in spite of its importance in the hydrological and the carbon balances, as the wet areas are an important water compartment which delays water transfer, modifies the sediment transport through sedimentation and erosion processes, and are a source for greenhouse gases. Remote sensing is a powerful tool for monitoring temporal variations in both the extent, level, and volume, of water using the synergy between satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 59 publications
(93 reference statements)
1
10
0
1
Order By: Relevance
“…For instance, the estimates of Yuan et al ( 2017b ) can differ up to 50% (average of ~ 30%) with the estimates from Lee et al ( 2015 ). Frappart et al ( 2021 ) suggested that the densification of the VS network over the Cuvette Centrale by including water elevation variations over the floodplains could impact the surface water storage by a factor four as compared to if only VSs over the rivers are used.…”
Section: Observing Surface Waters From Space In Africamentioning
confidence: 99%
“…For instance, the estimates of Yuan et al ( 2017b ) can differ up to 50% (average of ~ 30%) with the estimates from Lee et al ( 2015 ). Frappart et al ( 2021 ) suggested that the densification of the VS network over the Cuvette Centrale by including water elevation variations over the floodplains could impact the surface water storage by a factor four as compared to if only VSs over the rivers are used.…”
Section: Observing Surface Waters From Space In Africamentioning
confidence: 99%
“…The Congo Basin is one of the major river basins in the tropics. The atmospheric model datasets and satellite observations [ 52 , 53 ] play an important role in characterizing the basin’s hydro-climatological behavior since in situ hydrometeorological measurements are sparse in this region. However, it is not clear how the model resolution impacts the analysis and the understanding of the Congo Basin’s hydrology.…”
Section: Discussionmentioning
confidence: 99%
“…Des travaux sont en cours pour améliorer la cartographie des types de forêts et des tourbières. Les scientifiques du CIRAD exploitent des séries temporelles d'images acquises par des capteurs SAR (celui de l'altimètre Poséidon de Jason-2, développé en commun par la NASA et le CNES et le capteur SAR PALSAR-2 du satellite ALOS de JAXA), ce qui va leur permettre de faire une nouvelle description des différents types de forêts en fonction de leur inondation au fil du temps (Betbeder et al 2013 ;Frappart et al 2021). On a cherché par le passé à caractériser les tourbes à l'aide de données RADAR, notamment en détectant la formation de tourbières bombées (Siegert and Jaenicke 2008).…”
Section: Affiner L'état Des Connaissances Des Tourbières De La Cuvett...unclassified